Masalah Psikososial Remaja dengan Thalasemia Mayor: Literature Review - Allenidekania; Sartika, Nanda (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
Adolescent thalassemia majorhave a variety of psychosocial problems that have an impact ondecreasing QOL, interpersonal relationships, self-esteem resulting in depression. The aim of thisstudy is to look at psychosocial development and the things that occur in adolescent thalassemiarelated to psychosocial. Literature was made by analyzing scientific articles published from 2015-2019 and English. Data were obtained from Scopus, Wiley, Science Direct, Ebsco host, Proquestdatabases with psychosocial adolescent, thalassemia, and quality of life keywords. The results of theliterature study were 2,533 articles and 8 articles were obtained that fit the inclusion and exclusioncriteria. The results of the study are psychosocial problems occur due to activity restrictions, lack ofconfidence due to changes in face shape and skin color, adolescents feel different from siblings,decreased school performance. This will have an impact on the declining their QOL. The results ofthe literature review can be used as basic data in the development of counseling and mentoringprograms.